Investigating Warm and Humid Climate with the Approach of Production of Quantitative and Qualitative Architectural Models - Bahoush, Maryam; Salehabadi, Amir (Salehan Institute of Higher Education, 2018)
Climate change is one of the most significant threats facing the world today. Buildings are one of the largest energy consuming sectors in the world. Most contemporary buildings are highly dependent on air conditioning systems and electricity, reliant on fossil fuels and increasingly unable to adapt to a warming climate. Irans hot and cold climatic regions are vast. With the advancement of technology, life in every weather condition is possible. Humans can provide living conditions. Passive design responds to local climate and site conditions in order to maximize the comfort and health of building users while minimizing energy use. The key to designing a passive building is to take best advantage of the local climate. Passive cooling refers to any technologies or design features adopted to reduce the temperature of buildings without the need for power consumption. Today been proven that seasonal fossil contamination causes irreparable damage to our planets ecosystem, which is the result of global warming. According to studies conducted so far, the use of clean fuel cannot alone meet our needs in severe weather conditions. Eco-friendly architecture helps to save energy by avoiding energy losses. In this paper, with the careful analysis of weather information in Dezful, computer software solutions provide architectural solutions that can be measured and can be applied to each of the suggested patterns as Checked a number. Gaven Comfort conditions in this city without any static and dynamic system is 17.7% of the year, which can be increased by 78.8% of the year using static systems.